Energy and Economic Growth In Northern Sumatra - Giovanni Elvia Rahmah; Aliasuddin; Ernawati (International Journal of Economic, Technology and Social Sciences (Injects), 2026)
This study analyzes the influence of energy, unemployment, infrastructure, government expenditure, and investment on economic growth in the Northern Sumatra region (SUMBAGUT), which includes Aceh, North Sumatra, West Sumatra, Riau, and the Riau Islands. The study employs panel data from 2005 to 2024 and applies the Panel ARDL model to capture both short- and long-term relationships among variables. The estimation results indicate that, in the long run, energy, infrastructure, and government expenditure exert a suppressing effect on economic growth in the SUMBAGUT region. In the short term, energy, unemployment, infrastructure, government expenditure, and investment do not show statistically significant effects on economic growth. These findings suggest that economic growth in SUMBAGUT is strongly influenced by the quality of energy utilization, the effectiveness of infrastructure development, and the efficiency of government expenditure. The long-term suppressing effects of these variables reflect potential inefficiencies and resource misallocation. Moreover, the absence of significant short-term effects indicates that development policies require time to generate measurable impacts on economic activity. Therefore, more effective and efficient development policies are necessary to promote sustainable economic growth in the SUMBAGUT region.